2019
DOI: 10.1016/j.jtho.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

ROS1 Gene Rearrangements Are Associated With an Elevated Risk of Peridiagnosis Thromboembolic Events

Abstract: Introduction: This study aims to determine whether advanced ROS1 gene-rearranged NSCLC (ROS1þ NSCLC) has a higher than expected thromboembolic event (TEE) rate.Methods: Venous and arterial TEEs within ±365 days of diagnosis of ROS1þ, ALKþ, EGFRþ, or KRASþ advanced NSCLC at five academic centers in the United States and China were captured (October 2002-April 2018). The primary endpoint was incidence of TEE in ROS1þ compared to anaplastic lymphoma kinase (ALK)þ, EGFRþ, and KRASþ NSCLC within ±90 days of diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 14 publications
0
71
1
Order By: Relevance
“…overall and were the focus of this study). 24 This study concluded that the ROS1-mutant group had statistically significant, higher thrombotic event risk than the EGFR group (OR 2.44, 95% CI: 1.31-4.57, p ¼ 0.005) and KRAS group (OR 2.62, 95% CI: 1.26-5.46, p ¼ 0.01), but not the ALK group, which had similar risk (OR 1.45, 95% CI: 0.79-2.64, p ¼ 0.229).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…overall and were the focus of this study). 24 This study concluded that the ROS1-mutant group had statistically significant, higher thrombotic event risk than the EGFR group (OR 2.44, 95% CI: 1.31-4.57, p ¼ 0.005) and KRAS group (OR 2.62, 95% CI: 1.26-5.46, p ¼ 0.01), but not the ALK group, which had similar risk (OR 1.45, 95% CI: 0.79-2.64, p ¼ 0.229).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although this rate was relatively high, it was similar to the rates observed in other large studies evaluating thromboembolic events in unresectable or metastatic NSCLC. 24 Finally, there are numerous different molecular subtypes of NSCLC with varying biologic activity, and our control group was heterogenous, comprising all non-ALK molecular subtypes. Although this was sufficient for our goal of identifying whether ALK-rearranged tumors had a higher thrombotic risk than the general NSCLC population, it is likely that each molecular subtype imparts a distinct risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in order to demonstrate a direct correlation between ICIs and TE events, a control arm of patients with similar characteristics not receiving immunotherapy would have been optimal. However, this comparison is hard to perform, since NSCLC patients treated with chemotherapy are at even higher risk of TE events, as are patients with driver mutations receiving targeted therapies [54][55][56]. Moreover, if tested, lower rates of PD-L1 positivity would be found in these populations, as this might represent the reason to omit ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…200 Ng and colleagues also reported a higher incidence of thromboembolic disease in patients with ROS1 (34.7%) than patients with ALK (22.3%), EGFR (13.7%) or K-RAS (18.4%) mutations. 201 Overall, patients with ROS1 may have a better outcome with mOS of 3 years in those who had received only standard chemotherapy and over 5 years in those with both chemotherapy and crizotinib ( Table 3). 202 Crizotinib is the first TKI reported to have significant activity in ROS1 fusion mNSCLC.…”
Section: Ros1 Fusionmentioning
confidence: 99%